2014
DOI: 10.3390/antibiotics3030285
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Metallo-β-lactamases: Trends Revealed by Natural Diversity and in vitro Evolution

Abstract: The production of β-lactamase enzymes is one of the most distributed resistance mechanisms towards β-lactam antibiotics. Metallo-β-lactamases constitute a worrisome group of these kinds of enzymes, since they present a broad spectrum profile, being able to hydrolyze not only penicillins, but also the latest generation of cephalosporins and carbapenems, which constitute at present the last resource antibiotics. The VIM, IMP, and NDM enzymes comprise the main groups of clinically relevant metallo-β-lactamases. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 111 publications
(214 reference statements)
5
52
0
Order By: Relevance
“…An earlier study by Fast, Wang, and Benkovic (16) showed that a single mutation, C109R (C121R, according to the standard MBL numbering scheme [17]) in the MBL CcrA has a significant effect on the accumulation of nitrocefin intermediate and alters the rate-limiting step from the protonation to formation of I by ␤-lactam amide bond cleavage, which also results in altered k cat and K m under steady-state conditions. Thus, mutations of second-shell residues, such as 70, 121, 235, and 262, as they occur in the course of MBL evolution (18,19) certainly have a role in fine-tuning both the overall activity and catalytic pathway of these enzymes. As new ␤-lactams and MBL inhibitors, including mechanism-based inhibitors, are being developed, such subtle changes in the catalytic mechanism deserve our attention.…”
mentioning
confidence: 99%
“…An earlier study by Fast, Wang, and Benkovic (16) showed that a single mutation, C109R (C121R, according to the standard MBL numbering scheme [17]) in the MBL CcrA has a significant effect on the accumulation of nitrocefin intermediate and alters the rate-limiting step from the protonation to formation of I by ␤-lactam amide bond cleavage, which also results in altered k cat and K m under steady-state conditions. Thus, mutations of second-shell residues, such as 70, 121, 235, and 262, as they occur in the course of MBL evolution (18,19) certainly have a role in fine-tuning both the overall activity and catalytic pathway of these enzymes. As new ␤-lactams and MBL inhibitors, including mechanism-based inhibitors, are being developed, such subtle changes in the catalytic mechanism deserve our attention.…”
mentioning
confidence: 99%
“…These enzymes catalyze the hydrolysis of the amide bond in the ␤-lactam ring characteristic of this family of drugs (1)(2)(3)(4)(5). MBLs are metal-dependent hydrolases which generally use Zn(II) as a Lewis acid to activate a water molecule for the nucleophilic attack.…”
mentioning
confidence: 99%
“…Crystal structures of MBLs from the three subclasses have revealed that these enzymes present a common ␣␤/␤␣ sandwich fold, with the active site located within a groove at the interface between these two halves (1-6). The Zn(II)-binding residues vary among different subclasses, giving rise to diverse metal site architectures and metal contents required for activity (1)(2)(3)(4)(5)(6). B1 and B3 MBLs are broad-spectrum enzymes that hydrolyze penicillins, cephalosporins, and carbapenems with a wide variety of in vitro catalytic efficiencies, displaying a broad range of resistance profiles in vivo (1)(2)(3)(4)(5)8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first class B enzyme was isolated from an innocuous strain of Bacillus cereus (37). This protein, known as BcII, is the archetype, the most extensively studied model of enzymes of the largest ubiquitous and clinically relevant B1 subclass, such as VIM-, IMP-, and NDM-type MBLs (all transferable broad spectrum ␤-lactamases) (38). BcII consists of 227 residues in the mature form (M r ϭ 24,960/25,088 in the absence/presence of zinc ions), and its three-dimensional structure ( Fig.…”
Section: ؊1mentioning
confidence: 99%